ARMORUM STUDIUM: GLADIATORIAL TRAINING AND THE GLADIATORIAL LUDUS. (11th June 2018) - CARTER, MICHAEL
Abstract: In his Apologia (98.7), written about ad 158, Apuleius laments the fact that his former ward, the noble young Sicinius Pudens, has been allowed to abandon his studies and is instead spending his time in taverns and with prostitutes and, worst of all, has become a frequent visitor at the local gladiatorial school. Pudens has come to know all the gladiators' names, their 'fights and wounds', and has even started receiving instruction from the lanista himself. In this paper, I investigate the possible reasons why aristocratic Roman youth ( iuvenes ) might have sought weapons-training and the means by which these young men could have accessed such training in connection with a gladiatorial ludus . The investigation additionally considers the organization of gladiators and their trainers in the ludus .